1978
DOI: 10.1084/jem.147.3.882
|View full text |Cite
|
Sign up to set email alerts
|

On the thymus in the differentiation of "H-2 self-recognition" by T cells: evidence for dual recognition?

Abstract: The dual specificity of thymus-derived lymphocytes (T cells) for structures coded by the major histocompatibility gene complex (MHC) 1 and for foreign antigens (X) appears to be a general finding in mice and is likely to be a more universal phenomenon in higher vertebrates. Thus, all T-cell functions that have been tested in mice i.e., T cells involved in nonlytic helper, delayed type hypersensitivity, and macrophage activation functions are specific for the murine MHC (H-2) coded structure mapping to the I re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
250
4
1

Year Published

1979
1979
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 812 publications
(277 citation statements)
references
References 37 publications
22
250
4
1
Order By: Relevance
“…Whereas cellular and molecular mechanisms of T cell development at stages after TCR expression have been well clarified [36][37][38][39], relatively little attention had been directed to the earlier stages including lineage commitment. We have previously shown that T cell lineage restriction occurs at a prethymic stage [16-18, 40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas cellular and molecular mechanisms of T cell development at stages after TCR expression have been well clarified [36][37][38][39], relatively little attention had been directed to the earlier stages including lineage commitment. We have previously shown that T cell lineage restriction occurs at a prethymic stage [16-18, 40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Positive selection ensures that T cells respond to foreign antigens in conjunction with self-MHC molecules [1][2][3]. This is achieved by allowing T cells recognizing self peptides presented by self-MHC molecules to mature, resulting in differentiation of CD4 + CD8 + TCR low double-positive (DP) thymocytes into CD4 + CD8 -TCR high or CD4 -CD8 + TCR high singlepositive (SP) T cells [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Because continuous interaction between TCR and TCRrestricting MHC molecules is crucial for T cell selection and survival [6][7][8][9][10][11][12] and because it is known that cells expressing high-affinity TCR are much less susceptible to TCR-restricting MHC density [13,14], this study analyzed whether changes in TCR-restricting MHC density had a direct influence on the selection and survival of cells expressing low-affinity TCR. Experiments were therefore performed using the low-affinity [15] MHC class I H-2D b -restricted H-Y-specific transgenic TCR [16] under optimal and sub-optimal conditions.…”
Section: Introductionmentioning
confidence: 99%